Cross cultural adaptation and validation of burn specific health scale- brief in Nepali (BSHS-B-Np) - Regan Shakya; Misu Manandhar; Roshan Dangol; Archana Shrestha (SpringerOpen, 2020)
Abstract Background Burns are a global health problem affecting the survivors and disrupting many aspects of their lives. It is the second most common injury in rural Nepal accounting 5% of disabilities. Burn Specific Health Scale (BSHS) is a valid and most commonly used tool to measure Health Related Quality of Life (HRQoL) of the patient with Burns. BSHS- B (Brief) has been translated, culturally adapted and validated in multiple languages but not in Nepali. Therefore we aim to translate, culturally adapt and validate the BSHS-B in Nepali language (BSHS-B-Np). Methods Standard guideline was followed to translate the scale into Nepali language. One hundred eleven participants were evaluated to establish the psychometric properties of BSHS-B-Np. Internal consistency, test retest, content validity, discriminant validity and construct validity were assessed using Cronbach's alpha, Interclass correlation coefficient, Factor analysis, Spearman rank test, and Mann- Whitney U test respectively. Results The Cronbach's alpha for BSHS-B-Np was 0.93. Test retest inter-class correlation coefficient was between 0.92 and 0.98. The principal component factor analysis with varimax rotation resulted in separation of nine factors explaining 75.19% of total variance. BSHS-B-Np showed good discriminant validity in 35 out of 36 domain correlations confirming the construct of the scale. Furthermore, the scale was able to discriminate between face, upper limb and lower limb injury (p < 0.05). Conclusions BSHS-B-Np is a reliable and valid scale for Nepali burns survivors to assess their health related quality of life.